(m,n) - Type Holographic Dark EnergyBianchi Type-V Cosmological Model in General Relativity - M. C. Dhabe,; Kailas. R. Borgade,; A. I. Dethe, (International Journal of Scientific Research in Science and Technology, 2024)
Investigations currently underway aimed at the self-propelling study of type HDE cosmological model within the circumstance of theory of General Relativity (GR). The solutions of the field equations correspond to special form hybrid expansion law (HEL) which provides singular model. Also some physical and dynamical aspects and its behavior with the present day universe of the cosmological model have been discussed.
Keywords: (m,n) type HDE; General Relativity; Bianchi type-V metric